HUBUNGAN KADAR HEMOGLOBIN DENGAN PRESTASI BELAJAR MAHASISWA PROGRAM STUDI D-III KEBIDANAN DI UNIVERSITAS BATAM TAHUN 2017 - Yanti, Damai; Mona, Silvia (Universitas Batam, 2018)
Low hemoglobin is one of the health problems in the world. The iron deficirency can cause the optimum growth, learning ability, decreasing the ability to learn and getting low of intelligence quotions (IQ). This research aims to investigate the correlation of hemoglobin level and learning achievement. This research employs analytic survey by cross-sectional approach. The population involves the entire students in the 1 st and 2 ndyear of midwifery students. The data collecting technique in purposive sampling. The result the research reveals that from 57 respondent, there are 38 respondent posses hemoglobin level with no anemia and has satisfying learning achievement. While 19 respondent posses hemoglobil level with anemia and 16 respondent has the most satisfaction learning achievement and the rest of 3 respondent are statisying. The data analyzing technique is chi-square test with p value = 0,03 (<0,05) so the HO is refused. From the findings, it can be cocluded that there is correlation between. Hemoglobin level and learning achievement in suggestion, the student are expected to prevent anemia and their learning ability.